The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/yct.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Safety and Efficacy Data for a New Method of Performing Electroconvulsive Therapy

Abstract: ObjectiveElectroconvulsive therapy (ECT) is the most rapid and effective antidepressant treatment but with concerns about cognitive adverse effects. A new form of ECT, focal electrically administered seizure therapy (FEAST), was designed to increase the focality of stimulation and better match stimulus parameters with neurophysiology. We recently reported on the safety and feasibility of FEAST in a cohort (n = 17) of depressed patients. We now report on the safety, feasibility, preliminary efficacy, and cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…FEAST is a method of inducing a focal seizure using high-intensity direct current (Sackeim, 2004). The current passes from a small circular anterior electrode placed above the midpoint of the right eyebrow (right anterior orbitofrontal cortex) to a large oblong posterior electrode placed anteriorly to the right motor cortex (Sahlem et al, 2016). The effect is to induce a focal, frontal seizure as demonstrated by a regional cerebral blood flow study (Chahine et al, 2014).…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…FEAST is a method of inducing a focal seizure using high-intensity direct current (Sackeim, 2004). The current passes from a small circular anterior electrode placed above the midpoint of the right eyebrow (right anterior orbitofrontal cortex) to a large oblong posterior electrode placed anteriorly to the right motor cortex (Sahlem et al, 2016). The effect is to induce a focal, frontal seizure as demonstrated by a regional cerebral blood flow study (Chahine et al, 2014).…”
Section: Treatmentsmentioning
confidence: 99%
“…A feasibility study (Nahas et al, 2013) demonstrated the antidepressant efficacy of FEAST, with 8 and 5 of 16 patients reaching response or remission, respectively. A more recent study of 20 patients (Sahlem et al, 2016) demonstrated that FEAST was effective for depression, with response and remission rates of 65% and 55%, respectively. Furthermore, cognitive testing revealed no anterograde or retrograde memory side effects.…”
Section: Treatmentsmentioning
confidence: 99%
“…In severe cases in which an urgent and definite response is required, however, BT ECT can be chosen from the start. Some alternative placements, such as ‘left anterior right temporal’ (LART) and ‘focal electrically administered seizure therapy’ (FEAST) , should be considered experimental.…”
Section: Techniquementioning
confidence: 99%
“…Of interest, Focal Electrically Administered Seizure Therapy (FEAST) has recently been proposed which moves one electrode anteriorly close to the frontal electrode in fronto‐parietal placement. FEAST uses different sized electrodes and administration of a unidirectional rather than a bidirectional current . Recent pilot studies of FEAST also suggest that moving the temporal electrode to the frontal position may deliver an effective form of ECT with less cognitive effects .…”
Section: Discussionmentioning
confidence: 99%